Jagged1 Is Altered in Alzheimer's Disease and Regulates Spatial Memory Processing - Marathe, Swananda; Jaquet, Muriel; Annoni, Jean-Marie; Alberi, Lavinia (Frontiers in Cellular Neuroscience, 2017)
Notch signaling plays an instrumental role in hippocampus-dependent memory formation and recent evidence indicates a displacement of Notch1 and a reduction its activity in hippocampal and cortical neurons from Alzheimer’s disease (AD) patients. As Notch activation depends on ligand availability, we investigated whether Jagged1 expression was altered in brain specimen of AD patients. We found that Jagged1 expression was reduced in the CA fields and that there was a gradual reduction of Jagged1 in the cerebrospinal fluid (CSF) with the progression of dementia. Given the role of Notch signaling in memory encoding, we investigated whether loss of Jagged1 in neurons may be responsible for the memory loss seen in AD patients. Using transgenic mouse model, we show that the loss of Jagged1 expression during adulthood is sufficient to cause spatial memory loss and a reduction in exploration-dependent Notch activation. We also show that Jagged1 is selectively enriched at the presynaptic terminals in mice. Overall, the present data emphasizes the role of the Notch ligand, Jagged1, in memory formation and the potential deficit of the signaling ligand in AD patients.